2021
DOI: 10.1097/sla.0000000000004910
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in Surgical Education

Abstract: Objective: The objectives of this study were to review the coaching literature to (1) characterize the criteria integral to the coaching process, specifically in surgery, and (2) describe how these criteria have been variably implemented in published studies. Background: Coaching is a distinct educational intervention, but within surgery the term is frequently used interchangeably with other more established terms such as teaching and mentoring. Methods: A systematic search was performed of the MEDLINE and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Coaching has already become an established tool in the surgical education of medical students and trainees 6–8 . Yet in this review we will focus on coaching as a form of continued professional development (CPD).…”
Section: The Need For Surgical Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Coaching has already become an established tool in the surgical education of medical students and trainees 6–8 . Yet in this review we will focus on coaching as a form of continued professional development (CPD).…”
Section: The Need For Surgical Coachingmentioning
confidence: 99%
“…Coaching has already become an established tool in the surgical education of medical students and trainees. [6][7][8] Yet in this review we will focus on coaching as a form of continued professional development (CPD). The current avenues for CPD include conference attendance, scientific reading, research and audit participation and simulation skills labs training.…”
Section: The Need For Surgical Coachingmentioning
confidence: 99%
“…Although coaching is gaining attention in the domain of surgery, the implementation of coaching programs remains inconsistent in the literature . Recently, nonprofit organizations, such as The Academy for Surgical Coaching (https://surgicalcoaching.org), have promoted a theoretical framework for surgical coaching and provide specific training for coaches.…”
Section: Coachingmentioning
confidence: 99%
“…2 Although coaching is gaining attention in the domain of surgery, the implementation of coaching programs remains inconsistent in the literature. 3 Recently, nonprofit organizations, such as The Academy for Surgical Coaching (https://surgicalcoaching.org), have promoted a theoretical framework for surgical coaching and provide specific training for coaches. Several wellstructured peer-coaching programs implemented in North America have demonstrated that surgical coaching is well accepted and could have benefits for technical and nontechnical skills.…”
mentioning
confidence: 99%
“…Past reviews have included studies assessing coaching for surgeons in training, and have limited their scope to only include coaching interventions aiming to improve technical or nontechnical skills. 7 12 No previous review has evaluated coaching interventions for professional surgeons targeting any aspect of their professional skills or personal development. This scoping review aims to identify quantitative studies on coaching interventions for practicing surgeons to clarify how surgical coaching is defined, to analyze how these interventions are designed, implemented, and evaluated, and to illuminate relevant research gaps in the field.…”
Section: Introductionmentioning
confidence: 99%